2022
DOI: 10.1007/s40993-022-00420-y
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities for higher order differences of the logarithm of the overpartition function and a problem of Wang–Xie–Zhang

Abstract: Let $${\overline{p}}(n)$$ p ¯ ( n ) denote the overpartition function. In this paper, our primary goal is to study the asymptotic behavior of the finite differences of the logarithm of the overpartition function, i.e., $$(-1)^{r-1}\Delta ^r \log {\overline{p}}(n)$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…It is worth noting that despite the fact that the former proof requires more sophisticated preparation than the latter one, the method which we use there might be also effectively applied for more complicated functions like the partition function [22] or the overpartition function [28].…”
Section: Krystian Gajdzicamentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that despite the fact that the former proof requires more sophisticated preparation than the latter one, the method which we use there might be also effectively applied for more complicated functions like the partition function [22] or the overpartition function [28].…”
Section: Krystian Gajdzicamentioning
confidence: 99%
“…Moreover, these authors used that result and proved that the partition function p(n) is (asymptotically) r-logconcave for each r ∈ N + , for more details see [22]. Afterwards, Mukherjee, Zhang and Zhong [28] applied the aforementioned criterion and showed that the overpartition function is (asymptotically) r-log-concave for any r ∈ N + . Recall that an overpartition [9] of an integer n is a partition of n where the őrst occurrence of every distinct part may be overlined.…”
Section: Introductionmentioning
confidence: 99%
“…They also proved the higher-order Turán property of for (see [16, Theorem 1.2]). Following the treatment in [12], the first author [17, Theorem 1.7] laid out a proof that is 2-log-concave.…”
Section: Introductionmentioning
confidence: 99%